2022
DOI: 10.1097/cco.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Targeting exon 20 insertion mutations in lung cancer

Abstract: Purpose of reviewThe application of tyrosine kinase inhibitor (TKI) has successfully changed the standard of care in epidermal growth factor receptor (EGFR) positive non-small cell lung cancer. However, clinical survivals for patients with EGFR exon 20 insertions have failed to improve over the long period and the mutation appeared resistant to EGFR-TKIs. This overview focused on the current treatment strategies, summarized the emerging regimens for patients with EGFR exon 20 insertions, and demonstrated histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…The study of DZD9008 by Yang et al. ( 82 , 83 ) demonstrated that NSCLC patients with EGFR ex20ins had an ORR of > 40%, and the ORR for intravenous amivantamab (JNJ) was > 40%. The study also revealed that the ORR of EGFR ex20ins NSCLC patients treated with 300 mg QD of DZD9008 was 41.9%, whereas those treated with 200 mg QD of DZD9008 had an ORR of 45.9%.…”
Section: New Therapeutic Strategies For Patients With Nsclc Who Have ...mentioning
confidence: 99%
“…The study of DZD9008 by Yang et al. ( 82 , 83 ) demonstrated that NSCLC patients with EGFR ex20ins had an ORR of > 40%, and the ORR for intravenous amivantamab (JNJ) was > 40%. The study also revealed that the ORR of EGFR ex20ins NSCLC patients treated with 300 mg QD of DZD9008 was 41.9%, whereas those treated with 200 mg QD of DZD9008 had an ORR of 45.9%.…”
Section: New Therapeutic Strategies For Patients With Nsclc Who Have ...mentioning
confidence: 99%
“…In the follow-up, the company still needs to complete the communication with CDE, submit the new drug marketing application, complete the technical review, on-site verification and other procedures. 167 , 168 …”
Section: Covalent Regulationmentioning
confidence: 99%
“…In the follow-up, the company still needs to complete the communication with CDE, submit the new drug marketing application, complete the technical review, on-site verification and other procedures. 167,168 Rezivertinib (BPI-7711) ( 58) is an orally effective, highly selective and irreversible third-generation EGFR TKI. Rezivertinib shows highly selective inhibitory effects on EGFR Del E746-A750 , EGFR T790M , EGFR L858R/T790M double mutations, including EGFR single mutations, but shows a weak inhibitory effect on WT-EGFR.…”
Section: Covalent Egfr Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among rare mutations, EGFR ex20ins mutation is the most common. The incidence of EGFR ex20ins in EGFR mutated NSCLC patients is 4% -12%, while in NSCLC patients, the incidence is 1.8% -2.3% ( 3 ).…”
Section: Introductionmentioning
confidence: 99%